2005
DOI: 10.1116/1.1884125
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of superhard Ti–B–C–N films deposited by dc unbalanced magnetron sputtering

Abstract: Superhard quarternary Ti–B–C–N films were successfully deposited on AISI 304 stainless steel substrates by a dc unbalanced magnetron sputtering technique from a Ti–B–C composite target. The relationship between microstructures and mechanical properties was investigated in terms of the nanosized crystallites∕amorphous system. The synthesized Ti–B–C–N films were characterized using x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). These analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…The binding energy for a pure TiC phase is around 282.0 eV and that of amorphous carbon phase is located at ≈284.5 eV. The predominant peak at 283.2 eV can be due to the incorporation of carbon atoms to the TiB 2 phase forming the TiB x C y phase whose peak is shifted towards higher energies due to the different electronegativity between C and B as reported previously by other authors [33,34]. The x a-C fraction remains steady about 20% for the three first samples of the series and then increases continuously up to approximately 50%.…”
Section: Jc Sanchez-lopez Et Al (Paper B6-2-1)supporting
confidence: 65%
See 1 more Smart Citation
“…The binding energy for a pure TiC phase is around 282.0 eV and that of amorphous carbon phase is located at ≈284.5 eV. The predominant peak at 283.2 eV can be due to the incorporation of carbon atoms to the TiB 2 phase forming the TiB x C y phase whose peak is shifted towards higher energies due to the different electronegativity between C and B as reported previously by other authors [33,34]. The x a-C fraction remains steady about 20% for the three first samples of the series and then increases continuously up to approximately 50%.…”
Section: Jc Sanchez-lopez Et Al (Paper B6-2-1)supporting
confidence: 65%
“…In the case of the TiBC (see Fig. 4f), the C peak can be deconvoluted into three principal components at 282.2, 283.2 and 284.5 eV [33,34]. The peak structure was similar for all the coatings varying the relative intensities among the three main peaks.…”
Section: Jc Sanchez-lopez Et Al (Paper B6-2-1)mentioning
confidence: 99%
“…In this work, Ti-B-C-N coatings have been successfully synthesized using P-CFUBMS system and exhibit comparable super hardness and sliding coefficient friction to previous studies [7][8][9][10][11][12][13][14][15]. It was shown that the higher plasma density, ion current density and ion energies generated in the P-CFUBMS are benefit for improving the crystalline coating structure and properties [17,18].…”
Section: Mechanical and Wear Properties Of Ti-b-c-n Coatingsmentioning
confidence: 71%
“…Ti-B-C-N coating have been successfully synthesized by chemical vapor deposition (CVD) [4,5], electron beam physical vapor deposition (EB-PVD) [6], and more commonly by dc magnetron sputtering [7][8][9][10][11][12][13][14][15]. In recent years, the pulsed closed field unbalanced magnetron sputtering (P-CFUBMS) has become an important technology to produce advanced coatings due to its higher deposition rate, ion current and plasma densities, compared to conventional magnetron sputtering [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation